Chip War: The Fight for the World's Most Critical Technology - Demertzis, Maria (Journal of Economic Literature, 2024)
Maria Demertzis of Bruegel and European University Institute reviews “Chip War: The Fight for the World’s Most Critical Technology” by Chris Miller. The Econlit abstract of this book begins: “Promotes the argument that the contemporary world is defined by semiconductors, detailing how this technology has come to determine the shape of international politics, the structure of the world economy, and the balance of military power.”